In-vitro fit of experimental full-arch restorations made from monolithic zirconia - Schwindling, Franz Sebastian; Bechtel, Kevin Nikolas; Zenthöfer, Andreas; Handermann, Rebecca; Rammelsberg, Peter; Rues, Stefan (Journal of prosthodontic research, 2022)
Purpose: Fabrication inaccuracies can compromise the fit of large-span monolithic zirconia restorations. Sintering distortion is a particular problem. This study aimed to assess the fit of full-arch restorations made from monolithic zirconia for different abutment configurations.Methods: To quantify fit inaccuracies created during the fabrication of experimental large-span restorations, an in-vitro model with eight abutment teeth was equipped with strain gauges. Ten 14-unit restorations were made from monolithic zirconia and seated on the model in turn. For each of the ten restorations, measurements were taken for three different abutment configurations—polygonal, quadrangular, and unilaterally shortened. Strains exerted during seating were recorded in the anterior-posterior and buccal-palatal directions, and the resulting horizontal forces (rhF) were calculated along with the respective abutment deflection (ad). Data were analyzed using Kruskal-Wallis tests at a significance level of 0.05.Results: All restorations could be seated on the multi-abutment model. The restorations exhibited fabrication misfits, tending to be too wide. Mean rhF/ad were largest for the quadrangular configuration (16.8±2.9 N/0.065 mm) and smallest for the polygonal configuration (13.6±4.5 N/0.053 mm). The largest rhF/ad were measured on abutments of the unilaterally shortened configuration, with a maximum deflection of 0.126 mm. For two of three configurations, rhF/ad were significantly larger for the distal abutments than for the other abutments.Conclusion: Even if milling and sintering procedures are optimum, misfit-induced horizontal forces cannot be avoided. Because of the natural tooth mobility, however, the fit of full-arch restorations made from monolithic zirconia might be clinically acceptable.
Gesehen am 09.12.2022